Marfan syndrome: a therapeutic challenge for long-term care - Wagner, Andreas H.; Zaradzki, Marcin; Arif, Rawa (Biochemical pharmacology, 2019)
Marfan syndrome (MFS) is an autosomal dominant genetic disorder caused by mutations in the fibrillin-1 gene. Acute aortic dissection is the leading cause of death in patients suffering from MFS and consequence of medial degeneration and aneurysm formation. In addition to its structural function in the formation of elastic fibers, fibrillin has a major role in keeping maintaining transforming growth factor β (TGF-β) in an inactive form. Dysfunctional fibrillin increases TGF-β bioavailability and concentration in the extracellular matrix, leading to activation of proinflammatory transcription factors. In turn, these events cause increased expression of matrix metalloproteinases and cytokines that control the migration and infiltration of inflammatory cells into the aorta. Moreover, TGF-β causes accumulation of reactive oxygen species leading to further degradation of elastin fibers. All these processes result in medial elastolysis, which increases the risk of vascular complications. Although MFS is a hereditary disease, symptoms and traits are usually not noticeable at birth. During childhood or adolescence affected individuals present with severe tissue weaknesses, especially in the aorta, heart, eyes, and skeleton. Considering this, even young patients should avoid activities that exert additional stress and pressure on the aorta and the cardiovascular system. Thus, if the diagnosis is made and prophylactic treatment is initiated in a timely fashion, MFS and its preliminary pathophysiologic vascular remodeling can be successfully ameliorated reducing the risk of life-threatening complications. This commentary focuses on new research opportunities and molecular findings on MFS, discusses future challenges and possible long-term therapies.
Gesehen am 01.07.2019